The relationship between maximal oxygen uptake and repeated sprint performance indices in field hockey and soccer players - Aziz, A. R.; Chia, M.; Teh, K. C. (The Journal of Sports Medicine and Physical Fitness, 2000)
BACKGROUND: The purpose of this study was to examine the relationship between maximal oxygen uptake and repeated sprint performance in field hockey and soccer players. METHODS: Experimental design: a descriptive study on the aerobic-anaerobic performance of intermittent team game players. SETTING: the study was conducted at the Sports Medicine and Research Centre. Participants: forty male national team game players (22.6+/-4.2 years; 1.73+/-0.07 m and 63.7+/-6.2 kg) were involved in the study. Measures: all subjects completed a treadmill run test to exhaustion to determine maximal oxygen uptake and 8x40 m sprints either on the field or running track to determine repeated sprint ability performance. RESULTS: Body mass-normalised maximal oxygen uptake of 58.0+/-4.9 ml x kg(-1) x min(-1) of the group is comparable to values reported in the literature for team game players. No significant correlations were established between the fastest 40 m sprint time and maximal oxygen uptake (r=-0.21 and -0.08, p>0.05). Moderate correlations were established between maximal oxygen uptake and total time for the eight sprints (r=-0.346 and -0.323; p<0.05). CONCLUSIONS: Maximal oxygen uptake was not correlated with the fastest 40 m sprint time but was moderately correlated with total sprint time. Since the shared variance between maximal oxygen uptake and total sprint time was only 12%, improving aerobic fitness further will only be expected to contribute marginally to improving repeated sprint performance of the team game players. It remains possible that a high level of aerobic fitness enhances other aspects of match play in games like soccer and hockey.